A Real-Time Monitoring System for the Elderly based on the GSM Network - Ghassan Muslim Hassan (Newinera Publisher, 2022)
Infectious illnesses are more prevalent and harmful in older adults because to functional, demographic, and immunological changes brought on by aging. Treatment for these disorders is complicated by aging organ systems. Given that many seniors have multiple illnesses and take multiple medications, antimicrobial therapy for them should be carefully chosen to prevent drug interactions and other issues. Thus, it is important to keep an eye on the health of elderly people. In this research, we tracked elderly patients using a clever technique. The device includes a microprocessor, temperature sensor, pulse sensor, LCD display, and GSM module. The temperature and pulse of the elderly are shown on an LCD monitor. The system may notify emergency services if the pulse and temperature data go over the permitted limitations. The method was successfully tested on a large number of elderly persons.